IMPLEMENTASI METODE HADIAH DAN HUKUMAN DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA - Irma Darmayanti; Rafiah Arcanita; Siswanto Siswanto (Andragogi: Jurnal Pendidikan Islam dan Manajemen Pendidikan Islam, 2020)
This study aimed to find out a portrayal of the implementation of reward and punishment methods in increasing students’ motivation at MIS GUPPI 11 Rejang Lebong. This study used a qualitative approach. The data were gathered by means of observation and interviews. The data were analyzed by some stages, namely data reduction, data presentation and drawing conclusion. The conclusion of this study revealed: the fifth grade students’ learning motivation in learning akidah akhlak subject at MIS GUPPI 11 of Rejang Lebong increased better when the reward and punishment methods were applied. It was evident that the students participated in akidah akhlak lesson with good enthusiasm in attendance volume. They could express opinions in front of the class and complete assignments given by the teacher.